Ownership structure, political connection and firm performance: Evidence from Indonesia - Rusmin, R.; Evans, John; Hossain, M. (2012)
This paper investigates whether ownership structure and high levels of political connection in Indonesian firm's impacts on firm performance. Studying ownership structure in Indonesia is interesting for a number of reasons. Firstly, companies in Indonesia are owned by the families and corporate ownership structure is largely concentrated. Secondly, many companies in Indonesia have connections with politicians. Thirdly, little work has been done in Indonesia on the impact of foreign ownership on performance. Thus foreign ownership provides a unique setting for examining the monitoring role of foreign ownership as a substitute for corporate board monitoring. Using both accounting and market measures of firm performance we find that Indonesian firms with high political connections outperform Indonesian firms not politically aligned. Firms with significant foreign ownership performed better than domestic only owned firms. The results of the study support the findings that the governance of the largest government and foreign ownership firms not only acts to monitor management activities but also plays a representative role for monitoring shareholders.